1993
DOI: 10.1177/019372359301700107
|View full text |Cite
|
Sign up to set email alerts
|

Sport Participation and Women's Personal Empowerment: Experiences of the College Athlete

Abstract: As a result of gender-role socialization, women are often discouraged from viewing themselves as strong, competent, and self-determining individuals. Becoming empowered at the personal level would represent a foundation from which women could counteract these limiting self-perceptions as well as gain control over their lives. We explore the potential of sport participation to provide women with this increased sense of power. Telephone interviews were conducted with 24 women athletes in three Division Iintercol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 17 publications
1
39
0
Order By: Relevance
“…Blinde et al (1993) Hence. Blinde et al (1993) provide empirical, if subjective evidence that young women's sports involvement is linked to and indeed positively influences young women's views of their bodies (i.e.. functional body orientation).…”
Section: ^mentioning
confidence: 93%
See 4 more Smart Citations
“…Blinde et al (1993) Hence. Blinde et al (1993) provide empirical, if subjective evidence that young women's sports involvement is linked to and indeed positively influences young women's views of their bodies (i.e.. functional body orientation).…”
Section: ^mentioning
confidence: 93%
“…In their study of sports participation and the development of young women's personal empowerment, Blinde, Taub, and Han (1993) interviewed 24 intercollegiate athJetes. Blinde et al's results indicated that young women's sports involvement was related to young women's development of bodily competence (the degree to which participants reported having a strong and competent body) -a concept that is similar to the idea of body functionality.…”
Section: ^mentioning
confidence: 99%
See 3 more Smart Citations